2019
DOI: 10.1016/j.ijid.2019.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Increased body mass index linked to greater short- and long-term survival in sepsis patients: A retrospective analysis of a large clinical database

Abstract: Objectives: We investigated the impact of obesity (proxied as body mass index (BMI)), on short-and long-term mortality in sepsis patients. Methods: We conducted a retrospective analysis with adult sepsis ICU patients in a US medical institution from 2001 to 2012 in the MIMIC-III database. The WHO BMI categories were used. Multivariate logistic regression assessed the relationships between BMI and 30-day and 1-year mortality. Results: In total, 5563 patients were enrolled. Obese patients tended to be younger (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…Our findings are consistent with previous studies showing a protective impact of obesity on mortality in critically ill patients [20,21,[30][31][32]. However, the physiologic mechanisms behind these associations remain unclear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous studies showing a protective impact of obesity on mortality in critically ill patients [20,21,[30][31][32]. However, the physiologic mechanisms behind these associations remain unclear.…”
Section: Discussionsupporting
confidence: 92%
“…Despite predominantly negative associations, previous studies have also suggested obesity as a possible protective factor in sepsis and septic shock [20,21]. Biologically active and hormone secreting adipose tissue leads to alterations at both the cellular and the systemic level [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, we still cannot determine whether the interventions that patients have received before ICU admission may affect BMI, such as intravenous infusions. Compared with the inclusion criteria by ICD-9 code in the previous study [ 40 ], we used the sepsis-3 diagnostic criteria to enroll the study population. Moreover, our study took into account the effect of comorbidities, and, to our knowledge, this is the first time a U-shaped relationship between BMI and 28-day mortality has been found.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we retrospectively identified the septic patient dataset for developing SMRS from a single-center and excluded some patients due to missing data. A few of the variables were also excluded for the same reason, but previous research has shown that they might be associated with septic patients' mortality (e.g., BMI, albumin) (37,38). Third, in accordance with other severity scores, the timing of variable measurement was determined.…”
Section: Limitationsmentioning
confidence: 99%